The Predictive Value of Computed Tomography Findings for Poor Visual Outcome in Traumatic Eye Injury - Ping Ren; Yan Jiao; Chunling Zhang; Guoyue Chen (Journal of Ophthalmology)
Background. The prognosis of visual outcome is important for patients and healthcare providers and guides proper decision-making in traumatic eye injury. In this study, we have evaluated the predictive value of computed tomography (CT) scan findings for poor visual outcomes in patients with traumatic eye injuries. Methods. In a retrospective survey, documents of 200 patients with traumatic eye injury who underwent a diagnostic orbital CT scan were reviewed. Disorganized or collapsed globe, intraocular foreign body or gas, increased or decreased anterior chamber size, hemorrhage in the anterior or posterior chamber, crystalline or intraocular lens dislocation, posterior sclera thickening, globe borders haziness, orbital fracture, orbital hemorrhage, and foreign body, optic canal, and optic nerve injuries are the diagnostic clues for eye injury in CT scan. The predictive value of CT scan findings for poor visual outcome was calculated by sensitivity, specificity, accuracy, predictive values, hazard ratios, and binary logistic regression model. Results. The sensitivity, specificity, accuracy, and positive predictive values showed to be high. However, there was a low negative predictive value of CT findings for the prediction of poor vision. Among the investigated factors, disorganized/collapsed globe (HR 47.72, CI 6.13–371.62), increased/decreased anterior chamber size (HR 5.04, CI 2.57–9.88), hemorrhage in anterior/posterior chamber (HR 3.58, CI 1.900–6.774/3.62, CI 1.90–6.89), globe borders haziness (HR 3.06, CI 1.33–7.01), orbital foreign body (HR 3.66, CI 1.11–12.05), and optic canal/nerve injury (HR 21.62, CI 4.73–98.78) reached the statistical significance for increasing the hazard ratio for poor visual outcome in patients with a traumatic eye injury. Logistic regression analysis showed only evidence for disorganized/collapsed globe and optic canal/nerve injury in orbital CT scan as independent predictive factors for poor visual outcome. Conclusion. CT scan findings can be used as prognostic factors for visual outcomes in patients with a traumatic eye injury.